2022
DOI: 10.3389/fimmu.2022.870038
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells in Hepatic Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion injury can be divided into two phases, including insufficient supply of oxygen and nutrients in the first stage and then organ injury caused by immune inflammation after blood flow recovery. Hepatic ischemia-reperfusion is an important cause of liver injury post-surgery, consisting of partial hepatectomy and liver transplantation, and a central driver of graft dysfunction, which greatly leads to complications and mortality after liver transplantation. Natural killer (NK) cells are the lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…Experimental data revealed that during the initial phase of IRI in cold ischemia, NK cells significantly increased in the liver parenchyma but did not participate in tissue damage. During the following warm IRI, NK cell activation by NKG2D, along with increased inflammatory cytokines such as TNF-alpha, IL1, and IL6, was observed [58]. On the other hand, there was an upregulation of the TRAIL ligand in NK cells after IRI, which led to decreased neutrophil infiltration, IL6, and transaminase level, suggesting that NK cells play a role in immune tolerance after transplantation [79].…”
Section: Nk and Nkt Cells In Hepatic Irimentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental data revealed that during the initial phase of IRI in cold ischemia, NK cells significantly increased in the liver parenchyma but did not participate in tissue damage. During the following warm IRI, NK cell activation by NKG2D, along with increased inflammatory cytokines such as TNF-alpha, IL1, and IL6, was observed [58]. On the other hand, there was an upregulation of the TRAIL ligand in NK cells after IRI, which led to decreased neutrophil infiltration, IL6, and transaminase level, suggesting that NK cells play a role in immune tolerance after transplantation [79].…”
Section: Nk and Nkt Cells In Hepatic Irimentioning
confidence: 99%
“…DCs interact with T, NK, and NKT cells, while the latter might be correlated with IL10 and TGF-beta expression in an immunoreg- Distributed mainly in the perivenular and portal space, DCs are leukocytes that link innate and adaptive immune responses [57]. DCs interact with T, NK, and NKT cells, while the latter might be correlated with IL10 and TGF-beta expression in an immunoregulatory way [58]. Hepatic NK and NKT cells represent the predominant lymphocyte population.…”
Section: Innate Immune Cells In the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to provide a clinical solution to this problem, it is important to deeply investigate the pathogenesis of LIRI. LIRI can be divided into two phases, ischemia and reperfusion, which are characterized by hypoxia-induced cell injury in the ischemic phase and immunoinflammation after the restoration of blood flow [ 133 ]. During ischemia, ROS production as well as organelle damage, are induced by glycogen depletion, inadequate oxygen supply, and ATP depletion, which can lead to hepatocyte injury and death [ 134 , 135 ].…”
Section: Nlrp3 Inflammasome and Programmed Cell Death In Alimentioning
confidence: 99%
“…The liver is the center of numerous physiological processes, including nutrient metabolism, immune system support, lipid and cholesterol homeostasis, and the breakdown of xenobiotic compounds; [1] due to its multiple functions, the liver is in contact with exogenous and systemic substances continuously and is therefore highly exposed to injury and possible develop-ment of acute and/or chronic diseases. [2,3] The main damaging factors of the liver are viruses, high alcohol and drug consumption, an unbalanced diet, and metabolic and autoimmune diseases. Indeed, liver diseases constitute a major health problem, as they endanger human life; [4] these etiologies, together or individually, can trigger a cascade of liver diseases, from simple cellular damage to cirrhosis and even liver cancer.…”
Section: Introductionmentioning
confidence: 99%